Tobacco Control Measures' Role in Improving Employees' Health Under the Impact of Health Education and Media Campaign - Yu Wu (Frontiers Media S.A., 2022)
The overarching purpose of this study was to investigate the impact of health education, media campaigns, and peer counselor training on employees' health. This study also attempted to evaluate the function of tobacco control as a mediator in the relationship between employees' health and health education, media campaigns, and peer counselor training. Data were collected from 440 tobacco industry workers in China using a questionnaire technique. Smart-PLS software and a structural equation modeling (SEM) technique were used to evaluate the data. Employees' health was found to be significantly improved by health education, media campaigns, and peer counselor training. Furthermore, tobacco control was discovered to moderate the association between employee health and health education, media campaigns, and peer counselor training. By analyzing the impact of health education, media campaigns, and peer counselor training on employees' health, this research provided an important theoretical contribution. In terms of practical applications, this study would help employees consuming tobacco to maintain a healthy and safe atmosphere that encourages them to be engaged and perform well. Furthermore, this study could prove effective in resolving difficulties linked to controlling employee tobacco addiction and improving their performance. The tiny sample size of this study, which included solely employees working in the Chinese tobacco sector, was one of its limitations. In addition, future studies can incorporate other constructs to acquire a deeper knowledge of the factors that influence employees' health.